Formulasi Tablet Hisap Ekstrak Etanol Daun Sembung (Blumea Balsamifera (L.) Dc.) Dengan Variasi Konsentrasi Pulvis Gummi Arabicum Dan Manitol Serta Uji Antijamur Terhadap Candida Albicans - Yaminulloh, Sholeh; , Suprapto, M.Sc., Apt (2017)
The treatment of stomatitis aftosa are caused by Candida albicans is currently drops and mouthwash but differ with lozenges. Lozenges are an effective treatment for stomatitis aftosa in terms of both economic and comfort especially lozenges that contain active sembung this. Sembung (Blumea balsamifera (L.) DC.) has many benefits such as antimicrobial. This study aims to determine the ethanol extract lozenges formula sembung (Blumea balsamifera (L.) DC.) With a combination of binder PGA (Pulvis Gummi Arabicum) and sweetener mannitol and determine its activity against Candida albicans fungus before and after formulation. Extraction done by maceration method, and then testing the activity of the extract by the method of diffusion wells and the formulation lozenges comprising five formulas in composition variation binder PGA (Pulvis Gummi Arabicum) and sweetener mannitol ratio of each formula that is F1 (PGA 2, 5%; Mannitol 17.5%); F2 (PGA 5%; mannitol 15%); F3 (PGA 10%; mannitol 10%); F4 (PGA 15%; Mannitol 5%); F5 (PGA 17.5%; Mannitol 2.5%), manufacture of tablets by wet granulation method,. Testing the physical properties of the tablet include: organoleptic, uniformity of weight, hardness, friability, disintegration time with the processing of data using ANOVA test, test the responsiveness sense tablet with data processing using Friedman test. The results of this study are obtained sembung ethanol extract as much as 50.86 g with a yield of 4.23% w / w, the levels of 60 ug / mL to provide activity against Candida albicans fungus with inhibition zone of 10 mm, and the effect is not lost even done formulations. The test results lozenges have met all the physical properties of tablets required for lozenges, the requirements are: weight uniformity (CV <5%), hardness (10-20 Kg), friability (<1%), disintegration time (<30 minutes ). The best formula of this research is the formula 3 with mannitol levels and levels of PGA for tablet weight of 400 mg each at 40 mg / tablet